2017
DOI: 10.1139/cjm-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages: the possible solution to treat infections caused by pathogenic bacteria

Abstract: Since their discovery in 1915, bacteriophages have been used to treat bacterial infections in animals and humans because of their unique ability to infect their specific bacterial hosts without affecting other bacterial populations. The research carried out in this field throughout the 20th century, largely in Georgia, part of USSR and Poland, led to the establishment of phage therapy protocols. However, the discovery of penicillin and sulfonamide antibiotics in the Western World during the 1930s was a setback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 135 publications
(131 reference statements)
1
50
0
1
Order By: Relevance
“…In vitro studies showed that phage ZCEC5 was highly effective at reducing E. coli counts to below the detection limit when it is applied at MOI of 1 with producing high titers of phages. Our results are like the previous studies used bacteriophages to control bacterial infections . In this study, the most virulent phage was selected from an initial collection of 25 E. coli bacteriophages isolated from different environmental sources based on its strong ability to give lysis.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…In vitro studies showed that phage ZCEC5 was highly effective at reducing E. coli counts to below the detection limit when it is applied at MOI of 1 with producing high titers of phages. Our results are like the previous studies used bacteriophages to control bacterial infections . In this study, the most virulent phage was selected from an initial collection of 25 E. coli bacteriophages isolated from different environmental sources based on its strong ability to give lysis.…”
Section: Resultssupporting
confidence: 73%
“…The application of bacteriophage to control food‐borne disease is a promising strategy and dependent on the selection of appropriate phage . Bacteriophages are highly specific to their host organism and can be isolated from different environments where their hosts are available.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…,16 has been widely reviewed [17][18][19][20]. Phages are generally considered nontoxic to humans but not all phages are specific and unique advantages provided by nano-sized phages beginning with structure of the vectors, with a specific focus on display of foreign antigens on the phage surface.face of the phage where it retains its affinity and specificity for the target receptor.…”
mentioning
confidence: 99%